Analysis of ultra-triathlon performances - Rosemann T; Knechtle P; Knechtle B; Lepers R (Dove Medical Press, 2011)
Romuald Lepers1, Beat Knechtle2,3, Patrizia Knechtle2, Thomas Rosemann2 1INSERM U887, Faculty of Sport Sciences, University of Burgundy, Dijon, France; 2Institute of General Practice and Health Services Research, University of Zurich, Switzerland; 3Gesundheitszentrum St Gallen, St Gallen, Switzerland Abstract: Despite increased interest in ultra-endurance events, little research has examined ultra-triathlon performance. The aims of this study were: (i) to compare swimming, cycling, running, and overall performances in three ultra-distance triathlons, double Ironman distance triathlon (2IMT) (7.6 km swimming, 360 km cycling, and 84.4 km running), triple Ironman distance triathlon (3IMT) (11.4 km, 540 km, and 126.6 km), and deca Ironman distance triathlon (10IMT) (38 km, 1800 km, and 420 km) and (ii) to examine the relationships between the 2IMT, 3IMT, and 10IMT performances to create predicted equations of the 10IMT performances. Race results from 1985 through 2009 were examined to identify triathletes who performed the three considered ultra-distances. In total, 73 triathletes (68 men and 5 women) were identified. The contribution of swimming to overall ultra-triathlon performance was lower than for cycling and running. Running performance was more important to overall performance for 2IMT and 3IMT compared with 10IMT. The 2IMT and 3IMT performances were significantly correlated with 10IMT performances for swimming and cycling, but not for running. 10IMT total time performance might be predicted by the following equation: 10IMT race time (minutes) = 5885 + 3.69 × 3IMT race time (minutes). This analysis of human performance during ultra-distance triathlons represents a unique data set in the field of ultra-endurance events. Additional studies are required to determine the physiological and psychological factors associated with ultra-triathlon performance. Keywords: triathlon, swimming, cycling, running, ultra-endurance